Distraction in communication during discussion - Roslan, Nur Maisarah; Abd Rahim, Normaliza; Roslan, Nur Widad (Human Resource Management Academic Research Society, 2020)
Communication involves taking part in a discussion in order to learn, to help other people learn, to examiner issues, to share ideas, and to listen to the ideas and points of view of others. A discussion involves interaction among group members, a willingness to share ideas, and a willingness to respect others’ points of view. In other word, successful discussion involves leading and following, agreeing and disagreeing, contributing and questioning, exploring, expanding and focusing, evaluating, linking, responding, crediting, appreciating, and enjoying. However, distractions may happen in communication during discussion due to certain behaviours such as dominating, attacking, sarcasm about group members or their ideas, ridiculing, excluding, non-participation, lack of preparation, and often single-minded focus on task and many more. Therefore, this paper focuses on distraction in communication among secondary school students. The objectives of the study were to identify the theme and discuss the distraction during interaction. The samples of the study consisted of twelve subjects from a secondary school. The subjects were divided into groups of fours. They were given a task on storyboard for a video clip production. The activity took place in six weeks for three hours a week. The results of the study revealed that the subjects had given positive impact towards learning where they were actively involved in the task given.